Empirical Formulation of (n, p) Nuclear Cross-Section at 14â15Â meV - Hamid, M.A.B. (Springer Science and Business Media B.V., 2021)
The empirical equation of (n, p) nuclear cross-section is formulated at 14â15Â meV incident neutron energy. The data used for the construction of the empirical formula is obtained from EXFOR with a mass range of 9 < A< 111. From the data, we fit empirical formula with exponential dependency of (N-Z+AA)n where n is determined from the non-linear fitting. The empirical formulation is then compared using the chi-square coefficient as a quality criterion. The derived empirical formulation is compared with five previously published formulation. We show that the new formulation derived in this work gives good agreement with the experimental nuclear cross-section value. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.